MANAJEMEN KEPALA SEKOLAH DALAM MEMBENTUK KEPRIBADIAN SISWA DI SDN 31 BATU BULEK KECAMATAN LINTAU BUO UTARA - Dedi Dedi (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
The purpose of the study was to describe the planning, implementation and supervision of principals in shaping the personality of students in SDN 31 Batu Bulek, Lintau Buo Utara Sub District. This study uses a case study approach. This research belongs to the category of field research. This study uses a qualitative research approach. Collecting research data is done by observation, interview and documentation study. Research results (1). Planning Principals in shaping the personality of students by making planning characters to be formed, Planning in personality formation strategies, Planning in shaping student character based on student development, Factors considered in planning for the formation of student personality and Planning Principal in organizing the responsible Activities. (2). The implementation of the Principal in shaping the personality of students, with several programs, namely: Intensive teacher development, Involving Teachers in shaping the personality of students and Development of school culture. (3). Supervision of Principals in shaping the personality of students is done by controlling the personality of the teacher and students, controlling the principal in supervising the role of the teacher and controlling the principal in seeing the teacher's efforts and involving the teacher in the control.